Geopolitical changes and their implications for agricultural trade negotiations - Piñeiro, Martin; Piñeiro, Valeria (International Food Policy Research Institute, 2024)
The dissolution of the Soviet Union (USSR) in the 1990s marked a significant geopolitical shift, resulting in the clear and undisputed preeminence of the United States (USA) in global affairs. This new dominance was bolstered by the support of its closest allies, primarily the European Union (EU), Japan, Australia, and a few others.